Representation of Social Programs in Photojournalism: A Literature Review on Visual Framing in Online Media - Putra, Naufal Giri; Srikandi, Melati Budi; Maheswari, Anak Agung Istri Agung; Latupeirissa, Jonathan Jacob Paul (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the scholarly landscape of visual framing of social programs in photojournalism by examining publication trends, research themes, and influential institutions. Guided by PRISMA methodology, a structured search was conducted exclusively in the Scopus database, applying filters for peer-reviewed articles published in English up to July 2025. A total of 198 relevant studies were identified and subjected to bibliometric analysis using VOSviewer to visualize research trends, keyword co-occurrences, and collaboration networks. The results reveal a notable increase in publications since 2023, with a primary focus on social sciences, particularly communication and sociology, and significant contributions from leading institutions. Key themes identified include visual narratives, media effects, and digital platforms, underscoring the interdisciplinary nature of the field. The study highlights gaps in understanding how visual framing influences public perception and policy regarding social programs and recommends future research directions such as exploring emerging digital storytelling methods, cross-cultural comparisons, and technological innovations to deepen insights and improve the impact of visual communication in social advocacy.